Health-promoting behaviours and perceived lifestyle cancer risk factors among nurses. Issue 1 (February 2023) - Tong, Siaw Wei; Chui, Ping Lei; Chong, Mei Chan; Tang, Li Yoong; Chan, Caryn Mei Hsien
Abstract: Background: Nurses play a pivotal role in promoting health for cancer prevention. Comparatively little is known, however, of their health-promoting behaviours and perceived lifestyle-related cancer risk factors. Aim: To assess nurses' health-promoting behaviours and perception of lifestyle-related cancer risk factors. Methods: This is a descriptive, cross-sectional design study of 357 nurses from a teaching hospital. Respondents completed the Health-Promoting Lifestyle Profile II questionnaire. Perception of cancer risk factors was measured based on 29 well-established lifestyle factors. Findings: Almost half of all nurses were overweight or obese (mean BMI = 25.2, SD = 4.95). The highest health-promoting behaviour mean score was for the spiritual growth subscale, while the lowest mean score was in physical activity subscale. Lifestyle-related cancer risk factors such as overweight/ obesity, practising diets high in red meat or diets low in vegetables/ fruit, and insufficient physical activities were not prioritised by the nurses. Conclusions: Nurses in this sample were found to not engage in physical activity. A high proportion of nurses in this study attributed cancer risk to environmental rather than personal factors. The findings of the study enlighten nurse administrators in developing healthy lifestyle programs for nurses.